Expanding International Supply Chains The Role of Emerging Economies in Providing it and Business Process Services - Engman, Michael (OECD Trade Policy Papers, 2007)
Offshoring of business process services (BPS) and information technology services (ITS) - whether through international insourcing or international outsourcing - is transforming the way many companies do business. This paper looks at the expansion of international supply chains and the rise of China, the Czech Republic, India and the Philippines as exporters of BPS and ITS. It also analyses the nature of and factors behind this trade and identifies major business- and trade-related challenges arising. In this context it presents some of the labour market implications resulting from increasing trade between OECD and non-OECD economies. The analysis shows that the BPS and ITS sectors in the four emerging economies are very differently structured: Chinese and Czech companies are predominantly supplying their domestic markets while Indian and Philippine companies are focused mainly on supplying foreign markets.